The Effect of Interactive Media on Vocabulary Development Among Children: A Psycholinguistics Perspective - Duma Grace Simanjuntak; Bernieke Anggita Ristia Damanik (JURNAL ILMIAH NUSANTARA, 2025)
This comprehensive study looks at the effects of interactive media on language learning in children aged 1-3 years from a psycholinguistic standpoint. As interactive media becomes more integrated into early childhood education, it is vital to assess how technology affects language development, particularly vocabulary. The study uses a longitudinal mixed-methods approach to evaluate different types of interactive media, including educational apps, e-books, and interactive films. The findings show that children who used interactive media experienced considerable vocabulary gains, implying that well-designed media might be an effective aid for language development. However, the study emphasizes the risk of cognitive overload and distraction if media is not well regulated. The conversation provides valuable insights for educators, legislators, and instructional media designers, emphasizing the significance of balance and human interaction in early language development.